Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: 3x2 - 3y2 - 12x + 12y
= (3x2 - 3y2) - (12x - 12y)
= 3.(x2 - y2) - 12.(x - y)
= 3.(x - y).(x + y) - 4.3(x - y)
= 3.(x - y).(x + y - 4)
a) \(x^4-9x^2\)
\(=x^2\left(x^2-9\right)\)
\(=x^2\left(x-3\right)\left(^{ }x+3\right)\)
b) \(3x^2-12x+12\)
\(=3x\left(x^2-4x+4\right)\)
\(=3x\left(x-2\right)^2\)
c) \(x^2+5x+6\)
\(=x^2+3x+2x+6\)
\(=x\left(x+3\right)+2\left(x+3\right)\)
\(=\left(x+3\right)\left(x+2\right)\)
x4 - 9x2
= x4 - ( 3x )2
= ( x2 - 3x ) ( x2 + 3x )
b) 3x3 - 12x2 + 12x
= 3x3 - 6x2 - 6x2 + 12x
= 3x2( x - 2 ) - 6x ( x - 2 )
= ( 3x2 - 6x ) ( x - 2 )
= 3x ( x - 2 ) ( x - 2 )
= 3x ( x- 2 )2
c) x2 + 5x + 6
= x2 + 2x + 3x + 6
= x ( x + 2 ) + 3 ( x + 2 )
= ( x + 3 ) ( x + 2 )
1) 3x2y+6xy+3y= 3y.(x2+2x+1) = 3y.(x+1)2
2) 12x-4x2-9+a2 = a2-(4x2-12x+9)= a2-(2x-3)2= (a+2x-3).(a-2x+3)
3) x3-7x-6 = x3-2x2+2x2-4x-3x+6 = x2.(x-2)+2x.(x-2)-3.(x-2)= (x-2).(x2+2x-3) = (x-2).(x2+x-3x-3)= (x-2).(x+1).(x-3)
a) -7x2 + 5xy +12y2
=-7x2-7xy+12xy+12y2
=-7x(x+y)+12y(x+y)
=(x+y)(12y-7x)
b) x8 + 3x4 + 4
=x8+4x4+4-x4
=(x4+2)2-x4
=(x4-x2+2)(x4+x2+2)
=(x4+x2-2x2+2)(x4+x2+2)
=[x2(x+1)-2(x+1)](x4+x2+1)
=(x+1)(x2-2)(x4+x2+1)
a) 5x3 - 40 = 5( x3 - 8 ) = 5( x - 2 )( x2 + 2x + 4 )
b) x2z + 4xyz + 4y2z = z( x2 + 4xy + 4y2 ) = z( x + 2y )2
c) 4x2 - y2 - 6x + 3y = ( 4x2 - y2 ) - ( 6x - 3y ) = ( 2x - y )( 2x + y ) - 3( 2x - y ) = ( 2x - y )( 2x + y - 3 )
d) x2 + 2x - 4y2 + 1 = ( x2 + 2x + 1 ) - 4y2 = ( x + 1 )2 - ( 2y )2 = ( x - 2y + 1 )( x + 2y + 1 )
e) 3x2 - 3y2 - 12x + 12y = 3( x2 - y2 - 4x + 4y ) = 3[ ( x2 - y2 ) - ( 4x - 4y ) ] = 3[ ( x - y )( x + y ) - 4( x - y ) ] = 3( x - y )( x + y - 4 )
f) x3 + 5x2 + 4x + 20 = x2( x + 5 ) + 4( x + 5 ) = ( x + 5 )( x2 + 4 )
g) x3 - x2 - 25x + 25 = x2( x - 1 ) - 25( x - 1 ) = ( x - 1 )( x2 - 25 ) = ( x - 1 )( x - 5 )( x + 5 )
a) \(5x^3-40=5\left(x^3-8\right)=5\left(x-2\right)\left(x^2+2x+4\right)\)
b) \(x^2z+4xyz+4y^2z=z\left(x^2+4xy+4y^2\right)=z\left(x+2y\right)^2\)
c) \(4x^2-y^2-6x+3y=\left(4x^2-y^2\right)-\left(6x-3y\right)\)
\(=\left(2x-y\right)\left(2x+y\right)-3\left(2x-y\right)=\left(2x-y\right)\left(2x+y-3\right)\)
d) \(x^2+2x-4y^2+1=x^2+2x+1-4y^2\)
\(=\left(x+1\right)^2-4y^2=\left(x+2y+1\right)\left(x-2y+1\right)\)
e) \(3x^2-3y^2-12x+12y=3\left(x^2-y^2-4x+4y\right)\)
\(=3\left[\left(x^2-y^2\right)-\left(4x-4y\right)\right]=3\left[\left(x-y\right)\left(x+y\right)-4\left(x-y\right)\right]\)
\(=3\left(x-y\right)\left(x+y+4\right)\)
f) \(x^3+5x^2+4x+20=\left(x^3+5x^2\right)+\left(4x+20\right)\)
\(=x^2.\left(x+5\right)+4\left(x+5\right)=\left(x^2+4\right)\left(x+5\right)\)
g) \(x^3-x^2-25x+25=\left(x^3-x^2\right)-\left(25x-25\right)\)
\(=x^2\left(x-1\right)-25\left(x-1\right)=\left(x-1\right)\left(x^2-25\right)\)
\(=\left(x-1\right)\left(x-5\right)\left(x+5\right)\)
a)18x2-12x
=3x(6x-4)
b)3x2-11x+6
=x(3x-11+6)
=x(3x-5)
c)x3+6x2+11x+6
=x2(x+23
\(18x^2-12x\)
\(=6x\left(3x-2\right)\)
\(3x^2-11x+6\)
\(=3x^2-9x-2x+6\)
\(=3x\left(x-3\right)-2\left(x-3\right)\)
\(=\left(x-3\right)\left(3x-2\right)\)
a
\(3x^2-3y^2-12x+12y\)
\(=3\left(x^2-y^2\right)-12\left(x-y\right)\)
\(=3\left(x-y\right)\left(x+y\right)-12\left(x-y\right)\)
\(=3\left(x-y\right)\left(x+y-4\right)\)
b
\(x^2-3x-4\)
\(=\left(x^2+x\right)-\left(4x+4\right)\)
\(=x\left(x+1\right)-4\left(x+1\right)\)
\(=\left(x+1\right)\left(x-4\right)\)